2011
DOI: 10.1093/nar/gkr040
|View full text |Cite
|
Sign up to set email alerts
|

The histone H3K36 demethylase Rph1/KDM4 regulates the expression of the photoreactivation gene PHR1

Abstract: The dynamics of histone methylation have emerged as an important issue since the identification of histone demethylases. We studied the regulatory function of Rph1/KDM4 (lysine demethylase), a histone H3K36 demethylase, on transcription in Saccharomyces cerevisiae. Overexpression of Rph1 reduced the expression of PHR1 and increased UV sensitivity. The catalytically deficient mutant (H235A) of Rph1 diminished the repressive transcriptional effect on PHR1 expression, which indicates that histone demethylase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…A ChIP approach showed a 2-fold enrichment of Rph1-PA at the ATG7 promoter compared to Rph1 ΔZ -PA (Figure 5G). A similar enrichment was found at the PHR1 promoter, which was used as a positive control [30], but not at the non-coding region located at the tip of chromosome VI (ChrVI-260K), which was used as a negative control. This indicates that Rph1 directly binds the promoter region of ATG7 and that this binding is significantly reduced upon deletion of the zing-finger domains of the protein.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…A ChIP approach showed a 2-fold enrichment of Rph1-PA at the ATG7 promoter compared to Rph1 ΔZ -PA (Figure 5G). A similar enrichment was found at the PHR1 promoter, which was used as a positive control [30], but not at the non-coding region located at the tip of chromosome VI (ChrVI-260K), which was used as a negative control. This indicates that Rph1 directly binds the promoter region of ATG7 and that this binding is significantly reduced upon deletion of the zing-finger domains of the protein.…”
Section: Resultsmentioning
confidence: 77%
“…Previous studies showed that the transcriptional repression of some Rph1 targets is dependent on its histone demethylase activity [30]. We therefore proposed that Rph1 may repress ATG genes transcription, and thereby autophagy, in a similar manner.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Other studies show that Set2-dependent H3K36me3 is critical for appropriate resection and HR through recruiting repair factors CtIP (retinoblastoma binding protein 8), RPA (replication protein A1) and Rad51 (Jha and Strahl, 2014;Pfister et al, 2014). In the end, H3K36 demethylase Rph1 functions as a transcriptional repressor and inhibits the expression of DNA repair enzyme gene PHR1 and other stress-response genes by H3K36 demethylation, while DNA damage and environmental stress induce Rph1 phosphorylation and dissociation from chromatin to facilitate gene expression (Liang et al, 2011;Liang et al, 2013), indicating that H3K36 methylation is essential for DNA repair.…”
Section: Methylationmentioning
confidence: 99%
“…Additionally, the polycomb repressive complex 1, which contains Bmi1, Ring1, and Ring2, is required for H2A/H2AX ubiquitination (Bergink et al, 2006;Cao et al, 2005). Although the role of Ring1-mediated H2A ubiquitination in DNA damage response is not clear, Bmi1 and Ring2 are recruited to sites of DNA damage where they contribute to the monoubiquitylation of H2A/H2AX at Lys119/Lys120 (Ginjala et al, 2011;Pan et al, 2011). Bmi1/Ring2-dependent H2A/H2AX ubiquitination is critical for the localization of 53BP1, BRCA1 and other repair factors (Facchino et al, 2010;Ismail et al, 2010).…”
Section: Ubiquitinationmentioning
confidence: 99%